2021
DOI: 10.3390/app11041392
|View full text |Cite
|
Sign up to set email alerts
|

Saururus chinensis Prevents Estrogen Deficiency-Induced Osteoporosis in Rats: A Metabolomic Study Using UPLC/Q-TOF MS

Abstract: Saururus chinensis (SC), a traditional medicine, has been used for the treatment of edema, jaundice, gonorrhea, and several inflammatory diseases in China and Korea. Our previous studies reported the anti-osteoporotic activity of SC extract (SCE) in ovariectomized (OVX) rats but the mechanism of this effect was unclear. The aim of this study was to explore the anti-osteoporotic effect of SCE and elucidate the underlying mechanisms in ovariectomized rats using a metabolomics approach based on ultra-performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…More and more studies have verified that several lactic acid bacteria are capable of the biohydrogenation of linoleic acid ( 73 ). Recent study also revealed the prevention of PMOP in OVX rats by Saururus chinensis extract due to the involvement of linoleic acid ( 22 ). In our study, the GM significantly correlated to metabolites were belonging to two independent families Aerococcacease ( Globicatella ) and Lactobacillaceae ( Lactobacillus ) in the same order Lactobacillales of Firmicutes ( Figures 8 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more studies have verified that several lactic acid bacteria are capable of the biohydrogenation of linoleic acid ( 73 ). Recent study also revealed the prevention of PMOP in OVX rats by Saururus chinensis extract due to the involvement of linoleic acid ( 22 ). In our study, the GM significantly correlated to metabolites were belonging to two independent families Aerococcacease ( Globicatella ) and Lactobacillaceae ( Lactobacillus ) in the same order Lactobacillales of Firmicutes ( Figures 8 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…The significant correlations between GM and serum RANK, OPG and TRACP or inflammatory factors suggested a potential role of GM-bone axis in improving PMOP ( 21 ). More and more studies have also shown an influence of the altered GM on gut homeostasis via regulating bile acid, amino acid and fatty acid metabolisms, thereby leading to an improvement of PMOP ( 22 24 ). Correspondingly, those GM capable of bile acid, amino acid and fatty acid metabolisms were already used to prevent PMOP in OVX model ( 18 , 24 ).…”
Section: Introductionmentioning
confidence: 99%